Policy To Strengthen The National Defense System Through Improvements In The Capabilities Of The Indonesian Air Force's Passive Radar Systems - Fery Gustomo; Sri Yunanto; Usni Hasanudin (Journal Of Social Science (JoSS), 2026)
Changes in the global strategic environment and the increasing complexity of air threats require states to adopt adaptive defense policies oriented toward strengthening deterrence capabilities. In this context, passive radar represents a strategically relevant instrument, as it enables target detection without emitting signals, thereby enhancing survivability against low observable platforms and electronic warfare threats. This research aims to analyze the enhancement of the Indonesian Air Force’s passive radar capability as part of a broader strategy to strengthen the national defense system. This study employed a qualitative descriptive approach with a defense policy and strategic analysis framework. Data were collected through literature review and analysis of official defense policy documents. The findings indicate that passive radar holds significant strategic value within a layered air defense system; however, its utilization remains suboptimal due to policy limitations, insufficient system integration, human resource readiness gaps, and limited support from the national defense industry. The study recommends strengthening defense policies that position passive radar as an integral component of the national air defense strategy, enhancing human resource capacity, and reinforcing synergy among the Indonesian Air Force, the government, and the national defense industry. Optimizing passive radar capability is expected to enhance national deterrence and strengthen Indonesia’s strategic posture in safeguarding its airspace sovereignty.